GC-MS Analysis, Antiglycation, Antioxidant and Anti-lipid Peroxidation Activities of Harungana madagascariensis Methanolic Stem Bark Extract - Adetayo, Omotayo Mutiat; Modupe, Akoro Seide; Sunday, Adenekan; Cecilia, Ogundare Oyinlade; Aminat, Adesokan Ajoke; Bola, Olorode Isiwat (Trends in Sciences, 2023)
Plants’ natural products make excellent lead for the development of new drugs used for prevention, management and treatment of communicable and non-communicable diseases. The specific aim of the study was to investigate the antioxidant and antiglycation activities of Harungana madagascariensis methanolic stem bark extract. The active compounds present in the plant were extracted using methanol by maceration and resulting extract was subjected to phytochemical screening, antioxidant and antiglycation analysis. The extract was fractioned on silica gel to isolate the antioxidant compounds domiciled in the extract and fractions were identified by bioautography. The H. madagascariensis methanolic stem bark extract showed the presence of tannins, alkaloids, saponins, steroids and flavonoids. From the antioxidant assays, the extract scavenged 2,2-diphenyl-1-picryhydrazyl (DPPH) and nitric oxide radicals, inhibited lipid peroxidation in a dose dependent manner showing IC50 higher than ascorbic acid while it inhibited albumin glycation with IC50 lower than ascorbic acid. From the 12 fractions obtained only 7 fractions showed antioxidant activity and quercetin, flavone, 6-hydroxyflavone, ferulic and o-coumaric acid were inferred. From the GC-MS analysis, fatty acids and their esters, terpenoids and steroids were identified such as Hexadecanoic acid ethyl ester (6.53 %), 9,12,15-Octadecatrienoic acid (5.92 %), 9,12,15-Octadecatrienoic acid methyl ester (0.95 %), vitamin E (1.22 %), phytol (3.87 %), squalene (1.66 %) and Pregn-5-en-3-ol, 21-bromo-20-methyl-(3.beta.)- (1.94 %). In conclusion, H. madagascariensis methanolic stem bark extract possessed antioxidant and antiglycation activities, thus, can be used for new drug development to reduce or combat oxidative stress related diseases in humans. HIGHLIGHTS The methanolic stem bark extract of Harungana madagascariensis exhibited strong antiglycation and antioxidant activities Antioxidant compounds including flavonoids and phenolic acids (quercitin, flavone, 6-hydroxyflavone, ferulic and o-coumaric acid), terpenoids (vitamin E, phytol and squalene) fatty acids and their esters were found in the extract The stem bark extract of Harungana madagascariensis could be used as a source of antiglycation and antioxidant activity for new drug development in preventing oxidative stress related diseases and diabetic complications GRAPHICAL ABSTRACT